2015
DOI: 10.1111/ppa.12347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host and non‐host crops on Plasmodiophora brassicae resting spore concentrations and clubroot of canola

Abstract: Plasmodiophora brassicae, causal agent of clubroot of crucifers, poses a serious threat to Canadian canola production. The effects of fallow (F) periods and bait crops (clubroot-susceptible canola (B) and perennial ryegrass (R)) on clubroot severity and P. brassicae resting spore populations were evaluated in five sequences: R-B, B-R, R-F, B-F and F-F. Both host and non-host bait crops reduced clubroot severity in a subsequent crop of a susceptible canola cultivar compared with fallow. Resting spore and P. bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Several studies have reported that non-host crops could be used as baits to reduce the soil-infested resting spores (Friberg et al, 2006;Ahmed et al, 2011;Hwang et al, 2015). However, the underlying mechanisms are still not clear.…”
Section: Non-hosts Contain the Infection Of P Brassicae In Root Epidmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported that non-host crops could be used as baits to reduce the soil-infested resting spores (Friberg et al, 2006;Ahmed et al, 2011;Hwang et al, 2015). However, the underlying mechanisms are still not clear.…”
Section: Non-hosts Contain the Infection Of P Brassicae In Root Epidmentioning
confidence: 99%
“…Our results theoretically supported that the rotation of Brassica crops with non-host crops contributes to an integrative management to reduce the clubroot disease. In practice, the rotations with non-host crops barley, pea or oat not only reduced clubroot severity and resting spore concentrations, but also increased yield in contrast to continuous cropping of either resistant or susceptible canola (Hwang et al, 2015).…”
Section: Non-hosts Contain the Infection Of P Brassicae In Root Epidmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have estimated the half-life of resting spores of P. brassicae over time based on bioassays (Wallenhammar, 1996;Hwang et al, 2015). However, such bioassays are not suitable for a pathogen with a type III survival pattern because its survival is not constant over time or uniform among individuals in a population.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on soil conditions, infestation rate, pathogenicity of P. brassicae local strains and susceptibility of a crop's variety, yield losses can range from 30% to even 100% (Wallenhammar 1996). In control of the disease, the most important are preventive treatments including usage of pathogen-free fields, early pathogen detection, non-host crop rotation, use of the bait, decoy or catch crops, maintaining the appropriate soil pH and soil drenches with fungicides (Murakami et al 2000;Peng et al 2014;Hwang et al 2015). However, these methods would not reduce clubroot severity in heavily infested fields and they are not cost effective.…”
Section: Introductionmentioning
confidence: 99%